Konsep Keluarga Sakinah, Mawaddah, Warahmah dalam Tinjauan Psikologi - Fu’ad, Asep; Supriatna, Encup; Fahmi, Irfan (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
In Islam, the family is a spiritual institution that plays a central role in shaping human psychological and moral balance. However, modernization, individualism, and value disorientation have led to rising psychological crises and disharmony in Muslim households. This issue requires a scientific approach that goes beyond legal-normative perspectives toward an integrative psychological understanding. This study aims to analyze the concept of Sakinah, Mawaddah, and Rahmah from a psychological perspective to formulate a contextual and applicable model of family well-being. The research employs a qualitative library research method by synthesizing Islamic sources (Qur’an, Hadith, and classical scholarship) with contemporary psychological theories of emotional well-being and spiritual intelligence. The findings reveal that Sakinah represents spiritual-emotional equilibrium, Mawaddah functions as an ethical and transcendental affective energy, and Rahmah embodies compassionate empathy that nurtures healing and forgiveness. Together, these values constitute the Islamic Family Well-Being Model, an integrative paradigm that situates spirituality as emotional regulation, love as affective force, and compassion as moral regulator. This model asserts that genuine harmony in Muslim families can only be achieved through psycho-spiritual balance grounded in divine values.